Description of Erythrocyte Index Values in Chronic Kidney Disease Patients at Bendan Hospital, Pekalongan City - Fadhila, Arina; Wibowo, Subur (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Chronic Kidney Disease (CKD) is a condition characterized by the gradual and permanent decline of kidney function, which can lead to various complications, including anemia. Anemia in CKD patients is generally caused by reduced production of the hormone erythropoietin, iron deficiency, and the shortened lifespan of red blood cells due to the hemodialysis process. Erythrocyte index parameters, such as MCV, MCH, and MCHC, play a crucial role in determining the type of anemia in CKD patients. Method: This study used a descriptive design with a quantitative approach. The sample consisted of 30 CKD patients undergoing hemodialysis, selected using total sampling technique. Erythrocyte indices were examined automatically using a hematology analyzer. The data were analyzed and presented in the form of a frequency distribution table. Result: The examination results showed that the most dominant type of anemia was normochromic normocytic anemia (47%), followed by hypochromic microcytic anemia (37%), normochromic microcytic anemia (10%), and hypochromic normocytic anemia (6%). The average patient hemoglobin level was 8.4 g/dL and the average erythrocyte count was 2.7 million/µL Conclusion: The majority of CKD patients at Bendan Hospital, Pekalongan City, experience normochromic normocytic anemia. This finding highlights the importance of regular monitoring of erythrocyte indices to support the diagnosis and management of anemia in CKD patients.